Intermittent Hypoxia Mimicking Sleep Apnea Increases Passive Stiffness of Myocardial Extracellular Matrix. A Multiscale Study - Farré, Núria; Otero, Jorge; Falcones, Bryan; Torres, Marta; Jorba, Ignasi; Gozal, David; Almendros, Isaac; Farré, Ramon; Navajas, Daniel (Frontiers in Physiology, 2018)
BACKGROUND: Tissue hypoxia-reoxygenation characterizes obstructive sleep apnea (OSA), a very prevalent respiratory disease associated with increased cardiovascular morbidity and mortality. Experimental studies indicate that intermittent hypoxia (IH) mimicking OSA induces oxidative stress and inflammation in heart tissue at the cell and molecular levels. However, it remains unclear whether IH modifies the passive stiffness of the cardiac tissue extracellular matrix (ECM). AIM: To investigate multiscale changes of stiffness induced by chronic IH in the ECM of left ventricular (LV) myocardium in a murine model of OSA. METHODS: 2-month and 18-month old mice (N=10 each) were subjected to IH (20% O2 40s – 6% O2 20s) for 6 weeks (6h/day). Corresponding control groups for each age were kept under normoxia. Fresh LV myocardial strips (~7x1x1 mm) were prepared, and their ECM was obtained by decellularization. Myocardium ECM macroscale mechanics were measured by performing uniaxial stress-strain tensile tests. Strip macroscale stiffness was assessed as the stress value (σ) measured at 0.2 strain and Young’s modulus (EM) computed at 0.2 strain by fitting Fung’s constitutive model to the stress-strain relationship. ECM stiffness was characterized at the microscale as the Young’s modulus (Em) measured in decellularized tissue slices (~12 µm tick) by atomic force microscopy. RESULTS: IH induced a ~1.5-fold increase in σ (p<0.001) and a ~2.5-fold increase in EM (p<0.001) of young mice as compared with normoxic controls. In contrast, no significant differences emerged in Em among IH-exposed and normoxic mice. Moreover, the mechanical effects of IH on myocardial ECM were similar in young and aged mice. CONCLUSION: The marked IH-induced increases in macroscale stiffness of LV myocardium ECM suggests that the ECM plays a role in the cardiac dysfunction induced by OSA. Furthermore, absence of any significant effects of IH on the microscale ECM stiffness suggests that the significant increases in macroscale stiffening are primarily mediated by 3D structural ECM remodeling.